Cyanide test kit for cassava - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
A test kit for detecting cyanide levels in cassava has been developed in Australia to help Africans determine whether plants contain dangerous amounts of this naturally occurring poison. Cassava is an important staple crop in Africa, but each year...